Wide area digital dermoscopy applied to basal cell carcinoma, - Gerson Dellatorre; Guilherme Augusto Gadens (Sociedade Brasileira de Dermatologia, 2020)
Abstract In situations in when a dermoscopic record of a large lesion is desirable, the resulting images are usually restricted to a small field of view due to the limited diameter of dermatoscope lenses. This limitation often produces several photographs separately, thus losing the possibility of a single-image global evaluation. In these case reports, we show examples of a recently published image montage technique called Wide Area Digital Dermoscopy, in this case, applied to basal cell carcinomas.